Surface water resources of Santa Catarina southern region – Geochemical background of the coal mining territory - Cardoso, Albert Teixeira (2022)
In the environmental reclaiming process, it is essential to distinguish between concentrations of chemical elements that occur naturally in water resources (geochemical background), from those concentrations in which the presence of these elements results from anthropogenic activities. Despite the environmental efforts that have been carried out for more than two decades in the southern Brazilian region impacted by coal mining, its geochemical background is still not completely known. Filling this environmental knowledge gap was the objective of this work, which systematically analyzed the results of monitoring efforts carried out by the Geological Survey of Brazil (SGB/CPRM) across three years. Quality parameter distributions of rivers and streams unaffected by anthropogenic impact were analyzed. The database was used to perform principal component analysis (PCA) and cluster analysis, and to define the background values, which was done through the boxplot and ± 2 MAD (Median Absolute Deviation) methods. The results of multivariate statistical analyses clustered the monitoring sites into two groups, one related to the sedimentary rocks of the Paraná Basin and another to the crystalline basement rocks. The sedimentary group had a greater correlation with the parameters Eh, SO42-, Ca, Mg, EC, Mn, Acidity, Zn and Na; while, and the crystalline rocks group were better correlated with pH, Cu, Al, K, and Fe. The results of the geochemical background were similar for both methods, with values of pH, Fe, Al, and Mn being slightly different from those defined in Brazilian legislation (CONAMA 357/05 and MS 888/21).